Design of Brushless DC (BLDC) Motor Speed Control System Using Field Oriented Control (FOC) Method - Putra, Rokhmat Rizki Perkasa; Febrianto, Rokhmat (AI Society & STMIK Indonesia, 2026)
Research on environmentally friendly vehicles has highlighted Electric Vehicles (EVs), which utilize electric motors for propulsion. This study focuses on controlling a Brushless DC (BLDC) motor, a prevalent motor type in EVs, using the Field Oriented Control (FOC) method. The research aims to design and analyze the performance of this FOC-based speed control system. The system model and its control strategy were simulated in MATLAB/Simulink. Performance was evaluated under various speed setpoints (100, 200, and 300 rpm) and torque loads (2, 4, and 7 N.m). The results demonstrate that the proposed control system operates effectively, maintaining a steady-state error of less than 5% across all test conditions. Furthermore, all other performance parameters also remained below 5%, confirming the system's robustness and precision in regulating BLDC motor speed.